Bilateral temporomandibular joint reconstructions with stock alloplastic prostheses on a distracted mandible – A case report. Issue 4 (4th July 2022) - Kamath, Abhay T.; Kudva, Adarsh; Singh, Anupam
ABSTRACT: Background: The management of patients with a triad of temporomandibular joint (TMJ) ankylosis, retrognathia, and obstructive sleep apnea (OSA) has long been a matter of debate. Even though consensus favors distraction osteogenesis (DO) in the 1st phase of treatment to relieve the OSA, various treatment approaches for TMJ reconstruction after ankylosis release have been put forth. Most of the reconstructive modality has been focused on autogenous materials or customized TMJ prostheses after mandibular distraction. Case Presentation: The authors present a case of a patient with the triad of TMJ ankylosis, retrognathia, and OSA who underwent DO for correction of his OSA. This was followed by bilateral TMJ reconstruction with stock alloplastic prostheses on the distracted mandible, along with genioplasty to correct retrogenia. Conclusion: In this case, stock TMJ total joint prostheses were used successfully to treat bilateral TMJ ankylosis following previous surgery for mandibular distraction.